Functional dairy ingredients and nutraceuticals : physicochemical, technological, and therapeutic aspects - Goyal, M. R. (ed.); Veena, N. (ed.); Mishra, S. K. (ed.) (Apple Academic Press, 2023)
"Here is a comprehensive summary of new research and advancements in the unique functional and nutraceutical therapeutic and physiochemical aspects of dairy foods. The book explores the specific health benefits of dairy ingredients in nutraceuticals and functional foods as well as delves into production techniques that enhancement their therapeutic value. The first section of the book looks at the physicochemical and technological aspects of milk-derived components, discussing production, extraction and purification, and functional and technological applications of various functional dairy ingredients (such as lactulose, casein and whey protein-derived bioactive peptides). The volume also considers the therapeutic aspects of dairy ingredients, detailing the physiological and health effects of colostrum, oligosaccharides, conjugated linoleic acid, and lactoferrin. The third section focuses on enhancing the functionality of dairy foods by assessing the functional attributes that can be augmented by the addition of nutraceuticals such as probiotics, vitamins, and minerals or by the removal of cholesterol. Functional Dairy Ingredients and Nutraceuticals: Physicochemical, Technological, and Therapeutic Aspects provides an abundance of important research on the use of dairy ingredients in functional foods and nutraceuticals that will be valued by researchers, scientists, students, growers, traders, processors, industries, and others involved with the physicochemical, technological and therapeutic aspects of various nutraceuticals and functional dairy ingredients and their application in food and dairy industry"--
Keywords: Dairy Products; Functional Food; Dietary Supplements